Geschichte und Symbolik der gestreiften KZ-Häftlingskleidung - Schmidt, Bärbel (2000)
The subject of this study is the striped uniform of former concentration camp inmates which is an important feature of collective memory, symbolizing the industrialised mass murder committed by Germans. Premised on the assumption that textile objects are an important and specific source of contemporary history this thesis pursues the transformation of these garments from relic to 'memorial of today'. The analytical focus is on the tension between relic (i.e. the prisoner's garb as a source of history) and memorial (i.e. the prisoner's garb as a symbol). In comprehensively documenting striped uniforms stored or on exhibit in memorials and museums, an up-to-date survey is provided on how they came to be handed down and how they are described. At the same time problems as to the striped garbs original composition and structure, their production and distribution and their effects, and, last not least, their current presentation in exhibitions are discussed. The study includes a volume with illustrations and a catalogue documenting in detail 55 selected garments from the memorials at Auschwitz-Birkenau (Poland), Buchenwald, Dachau, Neuengamme, Ravensbrück, Sachsenhausen, from the Deutsches Historisches Museum, Berlin, from the Wewelsburg District Museum, Beit Lohamei Haghetaot and from the memorial Yad Vashem (Israel)